PLAYING AS A SOCIAL PRACTICE IDENITIFIED IN A GROUP OF RURAL CHILDREN - Zanotto, Luana; Alves, Fernando Donizete; Sommerhalder, Aline; Nicolielo, Maria Elisa; Limao, Juliana Inhesta [UNESP] (Univ Metodista Piracicaba-unimep, 2016)
This research aimed to identify and understand the educational processes built by children from rural, urban school students during the transfer from school bus going to school and return home. The group of participants consisted of fourteen children between 6 and 10 years old, students in the early years of elementary education at a public school located in Sao Paulo. He attempted to methodological foundation in qualitative research approach with participant observation inside the rural school bus. For systematization of information, records were made in a field diary. All the collected material was interpreted and categorized through content analysis. The results reveal that the play presents itself as the main educational process found inside the vehicle. The participating children experienced recreational experiences, teaching and learning from each other jokes of their daily life, they built themselves expressions of the group as the mode of communication and identity of that collective. Wonders how these educational processes, especially the experiences of rural children's play culture, produced by the children themselves are valued in the school context and indicates the need for production of new studies which intend to listen to children and teaching and learning processes generated by them in cohabitation with peers infant groups.
Keywords: EDUCATIONAL PROCESS; CHILDREN; RURAL ZONE; PLAY